Analysis of Student Computational Thinking Ability in PTIK UNS on Database Course - Daniel Enrique Triosandriawan; Dwi Maryono; Rosihan Ari Yuana (Journal of Informatics and Vocational Education, 2024)
This qualitative descriptive study aims to determine the computational thinking (CT) abilities of PTIK students in a database course and to identify differences in CT abilities among students with low, medium, and high academic grades. This research describes a condition based on existing research results and compares it with supporting theories to provide a systematic overview of the computational thinking abilities of PTIK FKIP UNS students. The research instruments included documents (database scores of PTIK students for the 2021 academic year) and essay test results from third-semester students who had completed the database course. The sampling technique used was purposive sampling. Data was collected through document analysis, test instruments, and in-depth interviews, with data validity tested using method and data source triangulation. The data was analyzed using narrative analysis techniques. The study assessed six aspects of CT ability in the database context: decomposition and reduction, abstraction, conversion and simplification, classification and division of ideas, reverse thinking, and assumptions. The results showed that, overall, PTIK students possess good CT skills. However, the abilities in reduction, simplification, and assumption could be improved. The research also found a clear difference between students with low midterm test scores and those with high midterm test scores. The data confirms that better grades in the database course correspond to better CT abilities among students.